Atypical cutaneous leishmaniasis: a new challenge to VL elimination in South-East Asia - Jain, Manju; Sangma, Diya A’gitok; Parida, Lipsalely; Negi, Rohit; Negi, Ajeet; Matlashewski, Greg; Lypaczewski, Patrick (Frontiers in Cellular and Infection Microbiology, 2024)
Visceral leishmaniasis (VL) caused by L. donovani in South-East Asian endemic countries including India, Nepal and Bangladesh has been the primary focus of the ongoing VL elimination program. With a major reduction in VL cases resulting from the elimination program during the last two decades, the efforts are now focused on the challenges posed by potential reservoirs within the asymptomatic cases, HIV-co-infection VL cases and Post Kala-azar Dermal Leishmaniasis (PKDL) cases that continue to sustain the parasite transmission cycle in known and newer endemic zones. This article brings attention to a new potential parasite reservoir in the form of atypical cutaneous leishmaniasis (ACL) cases caused by novel L. donovani genetic variants. L. donovani mediated ACL is an emerging phenomenon in recent endemic sites that now justify a need for implementing molecular surveillance tools to identify region-specific L. donovani variants with dermotropic capabilities and potential to revert to visceral disease. A timely detection of novel ACL causing L. donovani genetic lineages in South-East Asian endemic regions is necessary to halt the spread of ACL and is potentially crucial for the sustainability of the advances made by the VL elimination.